Audiovisual Media on the Marine Natural Potential of Pererenan Village Water for Entrepreneurship-Based Learning in Grade V Elementary School - Ni Putu Ayu Lenia Dewi; Gusti Ngurah Sastra Agustika; Ni Luh Putu Agetania (MIMBAR PGSD Undiksha, 2025)
The limited use of innovative instructional media by teachers has led to a lack of student interest in learning Science and Social Studies (IPAS), which often requires memorization-based cognitive engagement. This study aims to analyze the effectiveness of entrepreneurship-based audiovisual media in improving students’ learning outcomes on the topic of marine water resources. This research adopts a Research and Development (R&D) design using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The study involved 20 fifth-grade elementary school students as research subjects. Data were collected through interviews, observations, questionnaires, and multiple-choice tests, using validated instruments. The data were analyzed using quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistical analysis. The results showed that the tvalue (9.791) was greater than the ttable value (1.729), indicating a significant difference between the pretest and posttest scores. These findings confirm that the developed audiovisual media is effective in enhancing students’ academic performance. The study concludes that integrating entrepreneurship-based audiovisual media into instruction not only improves student learning outcomes but also strengthens the relevance of classroom content to real-life contexts and fosters the development of entrepreneurial values from an early age.